Pengaruh Debt Default, Kualitas Audit, Opini Audit, dan Pertumbuhan terhadap Opini Going Concern - Egy Septian; Sutabri, Tata (JUPITER (Jurnal Penelitian Ilmu dan Teknologi Komputer), 2025)
The problems in this research show that auditors experience difficulty in providing their opinions regarding the company's continuity. This is because the auditor's expectations are not met by the financial reports that are delivered in an indirect manner. Assessing debt default, audit quality, audit opinion, and company growth in relation to the acceptance of going concern audit opinions is thus made challenging by the auditor's doubts. The aim of this study is to examine how going concern audit opinion is affected by debt default, audit quality, audit opinion, and company growth. Secondary data from financial reports on the IDX website, www.idx.co.id, were used. Using a sample of manufacturing companies listed on the IDX between 2014-2016, a quantitative approach is employed. Using a purposive sampling technique, 143 samples were taken from the 27 companies that were included in the sample. audit quality, company growth, and audit opinion do not have a significant impact on going concern audit opinion: Debt Default, Audit Quality, and Audit Opinion. Furthermore, it has a significant positive effect on the going concern audit opinion, while company growth shows no impact. Given these findings, the researcher recommends that the sample size be increased and that other variables related to the going concern audit view be included in the subsequent study.   Keywords: Debt Default, Audit Quality, Audit Opinion, Company Growth, Acceptance of Audit Opinion Going Concern